Cyber Activism and Digital Identity: Navigating the Politics of Representation in Cyberspace - Khalil Zaman; Zara Ali (Yayasan Adra Karima Hubbi, 2025)
In an increasingly digital world, cyber activism and digital identity have become central to the discourse surrounding online participation and representation. The intersection of these concepts raises questions about how individuals and groups navigate the complex politics of visibility, power, and representation in cyberspace. This research explores how cyber activism influences the construction of digital identities and the political implications of online self-presentation. The study aims to analyze the relationship between cyber activism and the formation of digital identities, focusing on how these identities are constructed, contested, and performed in online platforms. It seeks to understand the impact of digital activism on political representation and personal agency in cyberspace. A qualitative research approach was employed, using case studies of prominent cyber activism movements, interviews with digital activists, and content analysis of social media campaigns. The study also draws on theoretical frameworks of digital culture, identity politics, and power relations in cyberspace. The findings reveal that cyber activism significantly shapes digital identities by providing platforms for marginalized voices and enabling new forms of political expression. However, challenges such as surveillance, cyberbullying, and digital censorship also complicate these efforts. Activists' online identities often face tension between authenticity and performative aspects of representation.